A Herpesviral Lytic Protein Regulates the Structure of Latent Viral Chromatin - Priya Raja (American Society for Microbiology, 2016)
ABSTRACT Latent infections by viruses usually involve minimizing viral protein expression so that the host immune system cannot recognize the infected cell through the viral peptides presented on its cell surface. Herpes simplex virus (HSV), for example, is thought to express noncoding RNAs such as latency-associated transcripts (LATs) and microRNAs (miRNAs) as the only abundant viral gene products during latent infection. Here we describe analysis of HSV-1 mutant viruses, providing strong genetic evidence that HSV-infected cell protein 0 (ICP0) is expressed during establishment and/or maintenance of latent infection in murine sensory neurons in vivo. Studies of an ICP0 nonsense mutant virus showed that ICP0 promotes heterochromatin and latent and lytic transcription, arguing that ICP0 is expressed and functional. We propose that ICP0 promotes transcription of LATs during establishment or maintenance of HSV latent infection, much as it promotes lytic gene transcription. This report introduces the new concept that a lytic viral protein can be expressed during latent infection and can serve dual roles to regulate viral chromatin to optimize latent infection in addition to its role in epigenetic regulation during lytic infection. An additional implication of the results is that ICP0 might serve as a target for an antiviral therapeutic acting on lytic and latent infections. IMPORTANCE Latent infection by viruses usually involves minimizing viral protein synthesis so that the host immune system cannot recognize the infected cells and eliminate them. Herpes simplex virus has been thought to express only noncoding RNAs as abundant gene products during latency. In this study, we found genetic evidence that an HSV lytic protein is functional during latent infection, and this protein may provide a new target for antivirals that target both lytic and latent infections.